Bukata M. V. Silence effect exteriorization in artistic discourse - Bukata M. V. (Philological Treatises, 2020)
The article deals with the nature of silence effect in artistic discourse (music, drama, painting). Perception of the given phenomena is analyzed through human senses. The attention is paid to intralingual and extralingual factors of silence effect exteriorization.